Effect of low-temperature treatments on photoluminescence enhancement of ion-beam synthesized Si nanocrystals in SiO₂ matrix - Khatsevich, I.; Melnik, V.; Popov, V.; Romanyuk, B.; Fedulov, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The results of experimental researches of photoluminescence (PL) spectra in Si nanocluster structures obtained by implantation of silicon ions to SiO₂-Si structures with high-temperature (1100 °C) and following low-temperature annealings in various regimes are given. We have found that additional low-temperature treatments in definite regimes result in substantial increase of the PL intensity, thus a maximum effect is observed after annealing in air. The possible mechanisms of the obtained effects are discussed. Those are based on supposition about the dominating contribution of luminescence through the electronic states on SiO₂-Si nanoclaster interfaces, which is related to defect and impurity complexes. It has been shown that growth of the PL intensity is governed by two effects: generation of new centers of radiative recombination on the nanocrystal-dielectric matrix interfaces, and passivation of nonradiative recombination centers.